Effect of task-specific execution on accuracy of imagined aiming movements. (12th January 2015) - Yoxon, Emma; Tremblay, Luc; Welsh, Timothy N.
Highlights: A common ideomotor network may link action imagination and execution. Imagined movement times (MTs) have been shown to decrease after execution. Present work studied how specificity of execution experience affects imagined MT. Imagined MT was reduced more when execution was specific to the imagined task. Abstract: Ideomotor theory states that the neural codes that represent action and the perceptual consequences of those actions are tightly bound in a common code. For action imagination, bound action, and perceptual codes are thought to be internally activated at a sub-threshold level through action simulation. In support of this hypothesis, previous research revealed that imagined movement times (MTs) for reciprocal aiming movements were closer to actual execution MTs after the participants gained experience executing the task. The current study examined the task-specific nature of the effects of experience on imagination by determining if improvements in accuracy in the imagination of reciprocal aiming movements occur only with experience of the reciprocal aiming task or with any aiming task. To this end, one group of participants executed a reciprocal pointing task, whereas a second group executed a discrete aiming task with comparable accuracy requirements before and after imagining reciprocal aiming movements. Influence of task specificity on imagination was assessed by evaluating the changes in imagined MTs before and after execution. Consistent with previous findings, there was a reduction in imagined MTs following task execution. Critically, there was a significant time by group interaction revealing a significant pre/post reduction in imagined MTs for the group that executed the reciprocal aiming movements, but not for the group that executed the discrete aiming movements. These data support ideomotor accounts of action imagination because it appears that the imagination of a movement is affected by task-specific experience with that movement.